FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KETIDAKJUJURAN AKADEMIK : MODIFIKASI THEORY OF PLANNED BEHAVIOR (TPB) - Yanti Trie Handayani; Zaki Baridwan (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this study was to examine the factors that influence the behavior of academic dishonesty . This study replicates a modified model of Theory of Planned Behavior ( TPB  ) developed by Beck and Ajzen (1991 ) . Theory of Planned Behavior ( TPB ) is a theoretical framework that examines the relationship between attitude , subjective norm , perceived behavioral control and moral obligation to behave interest and the relationship between interest behave towards academic dishonesty behavior . This study uses survey data collection with students in the Department of Accounting Faculty of Economics and Business UB as a population . A total of 169 of data ( questionnaire ) can be processed using smartPLS . The results showed that the attitude does not affect the behavior of interest . Meanwhile, subjective norm , perceived behavioral control and moral obligation affect the intention . Intention behave affects the behavior of academic dishonesty . The results of this study have an impact on the academic Department of Accounting Faculty of Economics and Business to consider the factor subjective norm , perceived behavioral control and moral obligation in determining the policy to minimize behaviors that occur in academic dishonesty among students . Keywords : Theory of Planned Behavior (TPB), attitude,subjective norm, perceived behavioral control, moral obligation, intention, academic dishonesty.